Analysis of E-Wallet Growth As a Cashless Transaction In Indonesia: Literature Review - Eliza, Rispa; Zulkifli Z; Elfiswandi, Elfiswandi; Fitria, Lailani; Lusiana, Lusiana; Sari, Silvia (Dinasti International Journal of Management Science, 2024)
This research aims to analyze the growth of e-wallets as cashless transactions in Indonesia. This research applies a qualitative descriptive method, namely describing the theory obtained as well as library research, which means looking for article sources that are related and relevant to the title raised in analyzing data that will be carefully related to e-wallets which have been widely implemented in Indonesia. As well as using Mendeley to cite previous research so that article writing is neat and suitable for publication. The research results show that from the three factors above, namely: e-wallet analysis, driving factors, and estimates of e-wallet usage in the next few years, the growth of digital transactions cannot be avoided, what we need to do is adapt to it so that we can carry out our daily activities. day smoothly, which in this case is about fintech above. Therefore, we as a society should at least increase literacy in the financial sector so that we are not easily directed in bad directions when carrying out transactions.